1983
DOI: 10.1111/j.1526-4610.1983.hed2306258.x
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Influences on the Cephalic Circulation: Experimental Data From Cat and Monkey of Relevance to the Mechanism of Migraine

Abstract: SYNOPSIS Stimulation of the locus ceruleus produces vasoconstriction in the intracerebral circulation and vasodilatation in the extracerebral circulation. The latter is mediated by the seventh cranial nerve, involving a non‐cholinergic transmitter. These vascular changes are reminiscent of those occurring in migraine. Stimulation of the trigeminal ganglion or of the trigeminal divisions produces a reflex dilatation in the external carotid territory also mediated by non‐cholinergic fibers in the seventh nerve. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(81 citation statements)
references
References 15 publications
2
79
0
Order By: Relevance
“…Lance et al (11) suggested that brainstem centres such as the locus coeruleus and raphe nuclei influence the vascular changes and pain of migraine; heightened activity of the locus coeruleus might also facilitate sensory processing. The cerebral cortex is densely innervated by noradrenergic fibres from the locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
“…Lance et al (11) suggested that brainstem centres such as the locus coeruleus and raphe nuclei influence the vascular changes and pain of migraine; heightened activity of the locus coeruleus might also facilitate sensory processing. The cerebral cortex is densely innervated by noradrenergic fibres from the locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect could account for both the neurological symptoms of migraine and the observed changes in blood flow and vascular reactivity. 6 In fact, it has been shown that extracranial blood flow is increased by 50% during migraine headache compared with that of normal subjects. 7 Thus, an increase in blood flow at the site of the migraine may result from alterations in sympathetic tone.…”
Section: Commentsmentioning
confidence: 99%
“…The reason this temporary sympathetic blockade may have triggered migraine headaches 24 hours later can only be postulated from data obtained from previous studies. [5][6][7][8] Abnormalities in autonomic nervous system control have been well documented in migraine, even during the headache-free interval. This autonomic imbalance in migraine consists of markedly enhanced sympathetic sensitivity with nonsignificantly reduced parasympathetic activity during headache-free periods.…”
Section: Commentsmentioning
confidence: 99%
“…The brainstem became a focus of attention for migraine research about 20 years ago in several laboratories including ours [Lance et al, 1983] and there is increasing evidence that a ''perturbation'' [Raskin et al, 1987] of the brainstem may lead to migraine. Two brainstem centers have been implicated in this defect-the periaqueductal gray matter (PAG) [Welch et al, 2001] and the nucleus raphe magnus (NRM) [Ellrich et al, 2001]-through which the PAG may relay.…”
Section: Brainstemmentioning
confidence: 99%
“…It is fair to say that most neural theories have adhered to Liveling's idea that some form of increased activity, somewhere in the CNS, is the ultimate cause of migraine pain. Brain areas or nuclei that have come under suspicion include the cortex [Hardebo, 1991], the periaqueductal gray matter (PAG) [Welch et al, 2001], the raphe nuclei, including the nucleus raphe magnus (NRM) [Lance et al, 1983;MacKenzie et al, 1985], the locus coeruleus [Goadsby et al, 1982], the superior salivatory nucleus [Burstein and Jakubowski, 2005], and the thalamus [Shields and Goadsby, 2005].…”
Section: Neural Theoriesmentioning
confidence: 99%